1994
DOI: 10.1212/wnl.44.7.1309
|View full text |Cite
|
Sign up to set email alerts
|

Clomipramine ameliorates adventitious movements and compulsions in prepubertal boys with autistic disorder and severe mental retardation

Abstract: In an open, nonblind clinical trial, clomipramine reduced adventitious movements and compulsions in five previously medicated prepubertal boys with autistic disorder and severe mental retardation. Poorly adapted rating scales, interrater variability, subject heterogeneity, different treatment histories, and environmental stresses confounded the assessment of treatment effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Positive reports noted improvements in repetitive behaviors, aggression, social engagement, language, adventitious movements, and adaptive behavior. [26][27][28] In the largest of the open studies (n = 35 adults), 13 participants experienced adverse effects, with 3 reporting seizures. 27 Two of these participants had a preexisting seizure disorder that had been stabilized on anticonvulsants, and 1 experienced a new onset tonic-clonic seizures.…”
Section: Serotonergic Agentsmentioning
confidence: 99%
“…Positive reports noted improvements in repetitive behaviors, aggression, social engagement, language, adventitious movements, and adaptive behavior. [26][27][28] In the largest of the open studies (n = 35 adults), 13 participants experienced adverse effects, with 3 reporting seizures. 27 Two of these participants had a preexisting seizure disorder that had been stabilized on anticonvulsants, and 1 experienced a new onset tonic-clonic seizures.…”
Section: Serotonergic Agentsmentioning
confidence: 99%
“…Published open trial studies with the less selective medication clomipramine have shown inconsistent findings and some have indicated that younger children respond less well (Brasic et al, 1994). Significant improvements have been more consistently observed in open studies of the SSRIs (DeLong, Teague, & McSwain-Kamran, 1998;Steingard, Zimnitzky, DeMaso, Bauman, & Bucci, 1997), including improvements in both repetitive behavior in children with autistic disorders.…”
Section: Serotonin Reuptake Inhibitors (Antidepressants)mentioning
confidence: 99%
“…Published open trial studies with the less selective medication clomipramine have shown inconsistent findings and some have indicated that younger children respond less well [Brasic et al, 1994;McDougle et al, 2000]. Significant improvements have been more consistently observed in open studies of the SSRIs [Steingard et al, 1997;DeLong et al, 1998], including improvements in both repetitive behavior and social-communication symptoms.…”
Section: Medication Intervention Studiesmentioning
confidence: 99%